MATHEMATICAL MODEL - DIFFERENTIATED DIETARY NUTRITION - PERIOD OF PRENATAL DEVELOPMENT OF THE FETUS (Innovative Technologica: Methodical Research Journal, 2022)
The influence of priority factors is considered as: vitamins during the development of the fetus in three trimesters. An analysis was made of the dynamics of fetal development, taking into account the saturation of nutrients and vitamins in food. Investigated about the main factors affecting the development of the fetus; The main types of nutrients in products that provide a rational diet for pregnant women have been identified. A mathematical model of differentiated dietary nutrition for the period of prenatal development of the fetus has been developed.